Proceedings of AFAA Sixth General Conference - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
Proceedings of the AFAA (Association of Faculties of Agriculture in Africa) Sixth General Conference on Food Security and Agriculture Research in Africa Lome in November 1987 Copies of the Proceedings are available from AFAA, c/o Institut Agronomique et